Nurse’s role ensuring drug safety - Naujalytė, Roberta; Jasionytė, Gabija; Griškutė, Patricija; Jackutė, Gerda; Gudaitytė, Liepa; Gierasamovič, Zita (Slauga. Mokslas ir praktika, 2020)
Five aspects have the greatest impact on the safety of medicine. First and foremost, this is the ability to acknowledge one’s errors, to register them, to develop the prevention plan so that they should not occur again. For this purpose a safe and user-friendly system should be devised, which would enable the errors to be ‘depersonalised’. It is important to impart knowledge of the effect of medication to the nursing staff. Almost half the nursing staff feel a lack of such knowledge. After caution of administering medicine had decreased, due to fatigue, working overtime or night shifts, errors became more frequent, for example, medicines that are in similar packages are often mixed up. The environment of a hospital or any other health institution is of great significance to the quality of work of the nursing staff in ensuring the safety of administering medicines. According to the WHO (World Health Organisation), it is effective and good management of a hospital, proper distribution of work and qualitative communication that enables the nursing staff to avoid the largest part of medical and nursing errors.